Perawatan ODGJ Di Rumah Dengan Masalah Gangguan Halusinasi - Melyza Melyza; Renda Alghoniy Saputri; Presti Marsyandah; Puja Enjelina; Shevi Deonina Putri; Sasi Sugianto; Ade Herman Surya Direja (Jurnal Dehasen Untuk Negeri, 2024)
Hallucinations are perceptions where individuals are unable to distinguish between real and unreal perceptions, causing individuals to lose control of themselves. The family has an influence on the patient's recovery or recurrence if the family does not have good knowledge about hallucinations treatment and support for patients when controlling hallucinations. The purpose of this study was to explain the relationship between family knowledge about hallucinations treatment and family support on the patient's ability to control hallucinations. The method used is to select articles from various sources using the PICO technique and then adjust them to the inclusion and exclusion criteria that have been determined, namely articles published for a maximum of 5 years (2016 – 2021), full 278 text articles, using Indonesian and English, the theme of the article. family knowledge about treating hallucinations and family support for the ability to control hallucinations. Based on the analysis of the article, it was concluded that the patient's ability to control hallucinations was influenced by family knowledge about caring for family members who experienced hallucinations and the provision of good family support for patients.